Healthcare-associated infections in the first four years of a pediatric surgical intensive care unit - Serkan Atıcı; Sinan Kılıç; Kıvılcım Karadeniz Cerit; Gürsu Kıyan; Ahmet Soysal (Journal of Infection in Developing Countries)
Introduction: Healthcare-associated infections (HAIs) are a significant cause of morbidity and mortality, particularly among critical pediatric surgical patients. This study aimed to evaluate the incidence, distribution, types, and pathogens involved in HAIs, in a newly established pediatric surgery intensive care unit (PSICU).